Prevalence of nicotine dependence among adults in Karachi, Pakistan - Zia Shamsi, Adnan; Tasneem, Sumbul; Haider, Iqra; Aslam, Mah Rukh; Sarwar, Humera (International Journal of Endorsing Health Science Research, 2018)
Background: World Health Organization states that smoking is presently the major reason for the death of one in every ten adults worldwide. The most astounding commonness of smoking is found more in gatherings of young adults and falls consistently in more seasoned age populace. Experimentation of smoking is usually seen during adolescence, but sufficient understanding of factors analogous to early initiation remains indescribable. Dependence is a conduct in which a person or an individual has blunt control with destructive repercussion. A number of reasons contribute in continuation of this dependence property, the majority of which include friends and social circle. Methodology: The focus of the research study is to get into account the ramification, extensiveness and reasons behind smoking in specifically young adults. A cross-sectional study was conducted; data were collected through a self-designed questionnaire. A total of 153 university students were included with a response rate of 100%, having to mean age 22 ± 2 .14 years. Data were analyzed using SPSS ver. 20 and Microsoft Excel 2013.Cross-tabulation was done using Chi-square test and one sample t-test. Results: The study results indicate that majority of the subjects started smoking between the age group of 17 -20 years, under the influence of their social gatherings, mostly due to friend circle, while the other reasons may include family, stress, and anxiety. 67.2% smoke cigarette along with their friends while 26.4% of the respondents were habitual of smoking alone. Conclusion: There are many factors which influence the rate of nicotine dependence among students, the majority of which includes the absence of medical guidance, lack of will, family and friends habits and withdrawal effects.